HUBUNGAN DISIPLIN KERJA DENGAN KINERJA KARYAWAN DAIMA HOTEL PADANG - Setyaningsih, Feni (Journal of Home Economics and Tourism, 2014)
This study aims to: 1) Describe the employee discipline Hotel Daima Padang, 2) Describe the employee's performance Daima Hotel Padang, and 3) Analyzing there a positive and significant relationship between the work and performance of employee discipline Hotel Daima Padang. This research is correlational research. The population in the study were employees of Hotel Daima Padang totaling 50 people. The sample totaled 50 employees taking the total sampling technique. Data was collected using a questionnaire and analyzed through description and correlation analysis using SPSS. The results showed that: 1) Discipline Employees are in the good category (72%), 2) Employee Performance are the good category (56%), 3) Results Corelasi Product Moment test with significance level of 5%, there is a positive relationship and significantly between Discipline Working with Employee performance with r value of 0.0418 with the interpretation of the relationship is quite strong. Keyword: Discipline of Work, Employee Performance